Gewinnung und Aufbewahrung von abgepumpter Muttermilch - Springer, Skadi; Berns, Monika; Mildenberger, Eva; Rouw, Elien; von Gartzen, Aleyd; Weichert, Stefan; Abraham, Klaus; Hösemann, Cornelia; Damms, Antje; Ensenauer, Regina (Monatsschrift Kinderheilkunde, 2025)
Background Breast milk is the optimal nutrition and provides the infant in a natural way with all the nutrients necessary for growth and healthy development. Instructions suitable for daily use on how to obtain, store and handle expressed breast milk support parents in situations where the breastfed healthy infant is not able to suckle at the breast. They also help to ensure that the supply of breast milk can be integrated into everyday life as safely and easily as possible and with reasonable effort, at home, in the daycare facility or at work. Method On the basis of national and international recommendations, systematic reviews and other reliable study data on the collection, storage and handling of expressed breast milk, experts from the National Breastfeeding Committee evaluated the scientific evidence and derived recommendations for action, which are summarized in this statement. Recommendations The statement of the National Breastfeeding Committee supports breastfeeding mothers and lactation consultants with evidence-based recommendations and action measures on how breast milk can be safely collected and stored for later use at home or on the go. The recommendations are exclusively intended for use in the collection and storage of breast milk for the healthy own child.
Online veröffentlicht: 11. April 2025
Gesehen am 26.05.2025